The Most Common Dermatological Findings In Atopic Dermatitis - AL-Musawi, Hasan Nasir (Diyala Journal of Medicine, 2018)
Background: Atopic dermatitis (AD) is a common, chronic, relapsing, itchy, skin condition occurring in patients with a personal or family history of atopy. It varies widely in clinical presentation at different ages and places. Objective: To determine the most common minor dermatological findings in patients with atopic dermatitis. Patients and Methods: This descriptive study was done at Al-Imamain Alkadimain Teaching Hospital, out patient clinic of dermatology from 2nd of January 2014 to the 1st of May 2014. The study involved 136 patients,73 of them were males and 63 were females; their ages ranged from 1 to 20 years. All patients were diagnosed clinically by a dermatologist according to Hanifin and Rajka major and minor criteria of AD. All the patients were subjected to a questionnaire including the identifying data and examined for the skin manifestations of the disease. Results: Atopic dermatitis affect males 73(53.7%) more than females 63(46.3%). Age of the patients ranging from 1 to 20 years with a mean of 7.80 ±5.23SD, mostly affecting the age group less than 10 years 70.6 %, family history of atopy was positive in 69.8%. The most common dermatological manifestation was xerosis affecting 88 patients (64.7%) followed by face pallor, or erythema in 64 patients (47%) and hand dermatitis in 63 patients (46.3%). Most common sites involved by dermatitis were face in 84 patients (61.7%) followed by hands in 63 patients (46.3%). Conclusion: Atopic dermatitis (AD) has a wide spectrum of dermatological manifestations. Xerosis is the most common minor skin findings of AD & icthyosis was the least common. Many conventional minor features were found, but some occurred less frequently.